Fenofibrate and Diabetic Retinopathy - Knickelbein, Jared E. (Curr Diab Rep, 2016)
Diabetic retinopathy, a common and sight-threatening microvascular complication of diabetes mellitus, is a leading cause of blindness among working-aged adults. Medical therapies including intensive control of hyperglycemia and hypertension have been shown to reduce the incidence and progression of diabetic retinopathy. The association of dyslipidemia and treatment with statins with diabetic retinopathy is inconsistent in epidemiologic studies. However, two recent randomized clinical trials have demonstrated beneficial effects of systemic fenofibrate therapy in reducing the progression of diabetic retinopathy independently of serum lipid levels. These findings suggest that fenofibrate may be an effective strategy for reducing the progression of diabetic retinopathy, thus reducing the large and growing public health burden of treating the sight-threatening complications of diabetic retinopathy.